PEMBACAAN SEMIOTIKA NOVEL LAYALI ALFU LAILAH KARYA NAJIB MACHFUDZ - Eva Farhah; Reza Sukma Nugraha; Muhammad Yunus Anis; Tri Yanti Nurul Hidayati (Translation and Linguistics (Transling), 2021)
Najib Machfudz is an Egyptian writer whose majority of his works are philosophical. His philosophical works cannot be separated from their influence on the thoughts of writers, thinkers and politicians. Readers of philosophical literary works certainly need their own understanding to be able to enjoy these literary works. One of the literary works that need to be understood by the readers is Layali Alfu Lailah by Najib Machfudz. The meaning of this work can be read by reading the semiotics of literature on the work. Thus, indirectly, this study aims to reveal the meaning of the novel Layali Alfa Lailah. The method for expressing this meaning is by reading heuristics and reading hermeneutics, or reading both of these is done directly together. As a qualitative research, this novel will be described according to the results of heuristic and hermeneutic readings and strengthened by explanations from secondary data supporting other analysis. Thus, the results of this study can be concluded that the novel Layali Alfu Lailah is a symbolic novel philosophy that concretely contains criticism and solutions from Najib Machfudz on the socio-political realities that occur around him and are experienced by the author. The benefit of this research is to provide examples of problems and alternative solutions to problems faced by a nation. This good example has a good influence on the readers.